The Community SOM Survey 1996: Centre - SOM Institute, University of Gothenburg (University of Gothenburg, 2001)
Every year since 1986, the SOM Institute carries out a nationwide survey, National SOM (Riks-SOM), in which people are asked questions about politics, society, their use of media, public service, the environment, risks, new media technology and their leisure-time activities. Since 1992 a corresponding survey is carried out in Göteborg and its surrounding communities: Western SOM (Väst-SOM). Starting in 1996, a local study, Community SOM (Kom-SOM), is carried out in different municipalities surrounding Göteborg as well as town districts in the city of Göteborg. Thus the results from the SOM surveys shed light on three levels of society: the national, the regional and the municipal. The questionnaire fr the 1996 Kom survey was divided into four subject fields: mass media; politics and society; leisure and housing; and background.

Varje år sedan 1986 genomför SOM-institutet en riksrepresentativ frågeundersökning på temat Samhälle, Opinion och Massmedia. Sedan 1992 genomförs en motsvarande frågeundersökning i Göteborg med kranskommuner: Väst-SOM. År 1998 utvidgades denna till att omfatta hela Västra Götalandsregionen samt Kungsbacka kommun. Utöver dessa undersökningar har SOM-institutet vissa år genomfört undersökningar i ett antal västsvenska kommuner samt stadsdelar i Göteborg, Kom-SOM. Kom-SOM utfördes för första gången under hösten 1996 i Göteborgsstadsdelarna Angered, Centrum och Majorna samt i Mölndals kommun. Kommunundersökningen är i huvudsak utformad på samma sätt som Riks- och Väst-SOM. Frågeformuläret är dock inte lika omfattande och urvalet är mindre. Många frågor är dock gemensamma för såväl de olika delarna av kommunundersökningen som för Riks- och Väst-SOM, vilket ger stora möjligheter till jämförelser mellan tre olika nivåer i samhället: nationell, regional och lokal. Frågeformuläret för Kom-SOM 1996 består av fyra sammanhållna delar: Massmedier; Politik och samhälle; Fritid och boende; samt bakgrundsfrågor.
SOM-undersökningen Kommun-SOM 1996: Centrum
Kom-SOM 1996
Keywords: housing; boende; public sector; offentlig sektor; culture; kultur; trust; förtroende; citizenship skills; medborgerliga färdigheter; political interest; politiskt intresse; local government services; kommunal service; newspaper readership; tidnings läsekrets; membership; medlemskap; access to information; tillgång till information; radio news; radionyheter; television news; tv-nyheter; privatization; privatisering; political influence; medborgarinflytande; political allegiance; politisk anhängare; television viewing; tv-tittande; religious affiliation; religiös tillhörighet; audio and video equipment; ljud- och videoutrustning; democracy; demokrati; leisure time activities; fritidsaktiviteter; commuting; pendling; radio listening; radiolyssnande; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap